Narrative Imagination of Islam in Nusantara: A Study on Islam in Babad Tanah Jawi and Babad Giyanti - Achmad Fawaid; Wening Udasmoro; Sri Margana; Miftahul Huda (Indonesian Journal of Islamic Literature and Muslim Society, 2023)
The lack of research on literary elements in "babad" is in line with the limited study of Islamic elements within this genre. This research aims to analyze the Javanese poets' depictions of Islam in "Babad Tanah Jawi" and "Babad Giyanti." The study operates under the assumption that "babad" as literary works can allegorically create a contested space where Islam interacts with other traditions. A qualitative paradigm with a comparative structural approach is employed in this study, focusing on the narratives that shape the author's understanding of Islam in the 18th century. The findings of this research reveal that the court poet's portrayal of Islam in "Babad Tanah Jawi" shares similarities with another work in the same genre, "Babad Giyanti." These commonalities encompass the utilization of Islamic verses in the "bhabuka" text and "asmaul husna," the depiction of "walisongo's" role, the practice of "tawajjuh," moral Islamic teachings, and the political positioning characterized by ambivalence and negotiation among different traditions.